2021
DOI: 10.51470/plantarchives.2021.v21.s1.265
|View full text |Cite
|
Sign up to set email alerts
|

] Role of Selection and Irrigation Periods in Improving Some Sunflower Characteristics Related With Drought Tolerance

Abstract: A field experiment was carried out at University of Baghdad -College of Agricultural Engineering Sciences in order to improve the drought tolerance characteristics of Sunflower using the two varieties, Shamos and Local, according to selection criteria; early flowering, low plant height and disk diameter under 10% selection intensity and three irrigation periods (5days, 8days, 10days). A split-plot according to Randomized complete block design was used with three replicates during the spring season of 2019 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
1
0
0
Order By: Relevance
“…This, in turn, negatively affected dry matter accumulation (Table 6) and its reduction, and hence the decrease in crop growth rate (Table 7). These results are consistent with those of [30,31,20,28,21,32,33) , who found that water stress causes a reduction in dry weight and hence a decrease in the growth rate of corn plants.…”
Section: Discussionsupporting
confidence: 92%
“…This, in turn, negatively affected dry matter accumulation (Table 6) and its reduction, and hence the decrease in crop growth rate (Table 7). These results are consistent with those of [30,31,20,28,21,32,33) , who found that water stress causes a reduction in dry weight and hence a decrease in the growth rate of corn plants.…”
Section: Discussionsupporting
confidence: 92%
“…Traditionally, sunflower is spring crop but can also be grown in the fall season. In Iraq, it is the second important oil crop after maize and grown of area (22 thousand hectors), and yield about 17 thousand tones [1]. The oil production is the most economically important traits and the focus of many sunflower breeding methods.…”
Section: Introductionmentioning
confidence: 99%